Do what thou wilt shall be the whole of the law: raul seixas's contributions to the study of law / Faça o que tu queres pois é tudo da lei: contribuições de raul seixas para o estudo do direito - Oliveira, Amanda Muniz; Rodrigues, Horácio Wanderlei; Grubba, Leilane Serratine (REVISTA QUAESTIO IURIS, 2019)
Abstract This article aims to demonstrate how rock, a media product derived from mass culture, can be used as a vehicle of social struggle, based on the example of Raul Seixas. Having achieved public success in the Brazilian dictatorial period, the artist tried to use his social status and his audience to disseminate ideals related to individual freedom. Knowing the Law of Thelema, Raul recreated this esoteric postulate and applied it in the social and political field, in order to diffuse its premises as a form of struggle and resistance against the dictatorship. The article, in this sense, will propose the use of rock as a way of reflecting about the law. For this, methodologically, we will investigate how and why rock should be considered a promising source of legal studies; in the sequence, the Brazilian situation of the 70's will be contextualized, the most successful time of Raul Seixas, and we will investigate the way the artist used his prominent place to denounce and challenge the status quo. Keywords: Freedom; Law & Music; Raul Seixas; Rock; Legal knowledge. Resumo: O presente artigo busca demonstrar de que forma o rock, produto midiático fruto da cultura de massa, pode ser utilizado como veículo de contestação e luta social, a partir do exemplo de Raul Seixas. Tendo alcançado sucesso de público no período ditatorial brasileiro, o artista procurou utilizar seu status social e sua audiência para disseminar ideais relativos à liberdade individual. Conhecedor da Lei de Thelema, Raul ressignificou esse postulado esotérico e o aplicou no campo social e político, de modo a difundir suas premissas como forma de luta e resistência contra a ditadura. O artigo, nesse sentido, irá propor a utilização do rock como forma de se refletir sobre o direito. Para tanto, metodologicamente, se buscará investigar como e por que o rock deve ser considerado uma promissora fonte de estudos jurídicos; na sequência, será contextualizada a situação brasileira da década de 70, época de maior sucesso de Raul Seixas, e investigada a maneira como o artista utilizou de seu lugar de destaque para denunciar e contestar o status quo. Palavras-Chave: Liberdade; Direito & Música; Raul Seixas; Rock; Conhecimento jurídico.